Game-Assisted Multimodal Learning Efficacy on Arabic Vocabulary Mastery: A Pre-Experimental Study in Indonesian Islamic Elementary Education - Desal Putri Ramdhani; Agus Yasin; Siti Nurfadlilah; Andi Nurizzah Aqila; Alya Zulfani (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2026)
This study examines the effectiveness of a game-assisted multimodal learning approach implemented through the Fun Arabic Class program in improving Arabic vocabulary mastery among fifth-grade students at MI Nurussalam. Grounded in Game-Based Learning theory, this study employed an experimental method using a one-group pretest–posttest design involving 26 students selected through total sampling. The instructional treatment was conducted over four learning sessions, integrating video-based learning, picture-matching games, and digital quizzes via Kahoot to support multimodal engagement. Data were collected using a validated Arabic vocabulary test with acceptable internal consistency reliability (Cronbach’s alpha = 0.82) and analyzed using the Wilcoxon Signed-Rank Test. The results indicated a statistically significant improvement in students’ vocabulary mastery, with mean scores increasing from 40.19 to 74.42 (p < 0.05), accompanied by a substantial median gain, indicating practical significance beyond statistical significance alone. These findings suggest that game-assisted multimodal learning can enhance student engagement and vocabulary retention in elementary Arabic instruction. However, the absence of a control group presents a potential internal validity limitation. Therefore, future studies are recommended to employ comparative experimental designs with larger samples to examine scalability and instructional effectiveness across different Arabic language competencies.